Hydration Properties of Portland Cement Paste with Boron Gangue - Quan Zhao; Jianwei Tu; Weiwei Han; Xi Wang; Youzhi Chen (Advances in Materials Science and Engineering)
In order to prepare a good radiation shielding concrete with a proper setting time and a high strength, the hydration properties of cement with boron gangue were investigated by the methods of XRD, isothermal microcalorimetry, TG/DSC, and FTIR. The results demonstrated that it was mainly related to the insoluble matter CaB2O4·4H2O and Ca(H2BO3)2·4H2O that boron gangue could severely inhibit the cement hydration. Boron gangue made a significant retardation on Portland cement hydration with the form of BO33− and BO45−, which caused an obvious retardation of C3A and C3S hydration with an insoluble coat and a low solubility of calcium ion in the solution. Therefore, it is important and necessary to take into consideration the chemistry of borates in aqueous and the kind of cement-based or cementitious materials used for radiation shielding concrete with boron or boron compounds, especially for the materials with a high content of C3A and C3S.